Computational Fluid Dynamics (CFD) Analysis of Electrolyte Flow Over Electroplating Surfaces with Integrated Flow Straighteners - ENG, SHAO TANG; Wan Saiful-Islam (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Electroplating is a critical process in semiconductor manufacturing, where the uniformity of metal deposition is directly governed by the distribution of electrolyte flow. Non-uniform flow often leads to current density variations and coating defects; therefore, this study utilizes Computational Fluid Dynamics (CFD) to optimize the design of integrated flow straighteners within a rectangular electroplating cell. Using the Shear Stress Transport (SST) k-ω turbulence model, a parametric analysis was conducted to evaluate the hydrodynamic effects of varying blade quantities and blade thicknesses. Flow uniformity was quantified using the Coefficient of Variation (CV) of velocity magnitude across the cathode surface. The results indicated that flow uniformity is non-linearly dependent on geometric parameters, with an optimal configuration identified at 23 blades and a blade thickness of 3.25 mm, achieving a minimum CV of 0.050. Furthermore, a dimensionless design correlation based on the Open Area Ratio, ∅ was formulated, revealing a theoretical optimum ratio of approximately 0.37. This finding establishes that the balance between flow guidance and blockage is the governing factor for uniformity, providing a robust, scalable engineering protocol for designing highprecision electroplating systems.